Retroviruses As Myeloid Cell Riders: What Natural Human Siglec-1 “Knockouts” Tell Us About Pathogenesis - Martinez-Picado, Javier; McLaren, Paul J.; Telenti, Amalio; Izquierdo-Useros, Nuria (Frontiers in Immunology, 2017)
Myeloid cells initiate immune responses and are crucial to control infections. In the case of retroviruses, however, myeloid cells also promote pathogenesis by enabling viral dissemination; a process extensively studied in vitro using HIV-1. This viral hijacking mechanism does not rely on productive myeloid cell infection, but requires HIV-1 capture via Siglec-1/CD169, a receptor expressed on myeloid cells that facilitates the infection of bystander target cells. Murine retroviruses are also recognized by Siglec-1, and this interaction is required for robust retroviral infection in vivo. Yet, the relative contribution of Siglec-1-mediated viral dissemination to HIV-1 disease progression remains unclear. The identification of human null individuals lacking working copies of a particular gene enables studying how this loss affects disease progression. Moreover, it can reveal novel antiviral targets whose blockade might be therapeutically effective and safe, since finding null individuals in natura uncovers dispensable functions. We previously described a loss-of-function variant in SIGLEC-1. Analysis of a large cohort of HIV-1-infected individuals identified homozygous and heterozygous subjects, whose cells were functionally null or partially defective for Siglec-1 activity in HIV-1 capture and transmission ex vivo. Nonetheless, analysis of the effect of Siglec-1 truncation on progression to AIDS was not conclusive due to the limited cohort size, the lack of complete clinical records and the restriction to study only off-therapy periods. Here we review how the study of loss-of-function variants might serve to illuminate the role of myeloid cells in viral pathogenesis in vivo and the challenges ahead.